BIOTECHNICAL SYSTEM FOR INTEGRATED OLFACTOMETRY DIAGNOSTICS - Yana Nosova; Oleg Avrunin; Valery Semenets (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is the process of olfactometric research of a human olfactory function. The object of the study is a biotechnical system which includes a method for increasing the objectivity of olfactometric diagnostics. The goal is to develop a biotechnical system for complex olfactometry, which enables increasing the objectivity of olfactometric studies and connecting breathing parameters with olfactory function by placing an odorant carrier in the airway of the rhinomanometer, as well as by using procedures for determining the energy characteristics of respiration. The methods used are: methods of digital signal processing, the theory of biotechnical systems. The following results are obtained. A structural diagram of a biotechnical system for olfactometric diagnostics of a human olfactory analyser was developed. As a result of the analysis of the cyclogram of nasal breathing, it is found that by changing the frequency and nature of breathing upon reaching the sensitivity threshold, it is possible to objectify the method of assessing respiratory and olfactory disorders according to the energy criterion of pneumatic power when inhaling appropriate odorivectors, and also to study the olfactory and respiratory function with the capability of estimating respiratory cycles in a dynamic mode. The studies were carried out on the basis of typical inspiration cycles: with a quiet breathing in the normal conditions, in the forceful breathing mode with a stiff nasal valve, with a nasal valve with natural functional mobility which restricts the flow of air, and also a stepped inspiration – a short “sipping” of air, which can be characterized as a kind of “sniffing”. Conclusions. Computer olfactometry is one of the most promising methods for diagnosing olfactory disorders of respiratory genesis. The developed biotechnical system is based on the use of a fundamentally new design, combining a rhinomanometer and an olfactometric nozzle with a container for an odorant. A feature of this system is also the capability to determine the energy characteristics of nasal breathing when the sensitivity threshold of the odorivector is reached. The future direction of the work is to specify the concentrations of odorants for the biotechnical system for olfactometric diagnostics, which enables testing the sensitivity of the olfactory analyser on outpatient basis.